The Impact of Concurrent Gleptoferron and Toltrazuril Injection on Hematological Profile, Health, and Growth in Pre-weaned Piglets - Ida Bagus Komang Ardana; Anak Agung Gde Jayawardhita; Anak Agung Gde Oka Dharmayudha; Anak Agung Sagung Kendran (Advances in Tropical Biodiversity and Environmental Sciences, 2024)
This study sought to assess the effects of simultaneous Gleptoferron and Toltrazuril administration on hematological parameters, health status, and growth performance in pre-weaned piglets. A total of 54 piglets aged 1 to 3 days were randomly allocated into three groups: a control group receiving a placebo injection, a group administered iron (Ferdex), and a group injected with Gleptoferron in conjunction with Toltrazuril (Forceris). Hematological markers, morbidity, mortality, and body weight growth were evaluated during a 20-day duration. The findings indicated that the administration of Gleptoferron and Toltrazuril markedly elevated red blood cell (RBC) counts, hemoglobin concentrations, and hematocrit levels relative to the iron-only group, without an increase in total white blood cell (WBC) counts, suggesting the absence of post-injection infection. Moreover, pigs administered Forceris did not develop hypochromic anemia and had a reduced incidence of diarrhea (6.7%) with no mortality, indicating enhanced gut health and excellent coccidiosis prevention. Significantly, pigs administered Forceris exhibited a weight gain of 9 kg at 20 days of age, in contrast to 7.9 kg in the iron-only cohort. The results indicate that the simultaneous use of Gleptoferron and Toltrazuril provides more advantages in avoiding anemia, improving growth, and fostering better health outcomes in pre-weaned piglets than iron supplementation alone. This efficient and pragmatic approach has significant ramifications for enhancing production in pig breeding operations